Biogenic Synthesis and Characterization of Zinc Oxide Nanoparticles using Tecoma stans Flower Extract and Harnessing its Antimicrobial Potential (Asian Journal of Pharmaceutics (AJP), 2025)
Aims: The present study focuses on the green synthesis of zinc oxide nanoparticles (ZnO NPs) using biocomponents extracted from the Tecoma stans flower. Among the extensively studied Nps, ZnO Nps have garnered significant attention due to their versatility in numerous downstream applications. The biomedical industry has witnessed a rapid surge in the utilization of nanotechnology, thanks to the unique and valuable properties offered by Nps. Materials and Methods: Fresh flowers were washed and then boiled in distilled water to get the filtrate, which was subjected to centrifugation at 8000 rpm. Next, 20 mL of plant extract was gradually added drop by drop to 80 mL of the 0.1 M zinc acetate solution while continuously stirring the mixture. A white crystalline precipitate formed at 50°C. The size of the nanocrystals was determined through X-ray diffraction (XRD) data using Debye–Scherrer’s formula. Results and Discussion: An eco-friendly method was employed to synthesize ZnO nanocrystals with an average size ranging from 12 to 44 nm and showed significant antibacterial activity. The synthesized zinc Nps were characterized using scanning electron microscopy and XRD. Conclusion: The ZnO Nps obtained exhibited a spherical shape and exhibited antimicrobial activity. These Nps hold great potential for a wide range of applications across various fields, such as biomedical imaging, wastewater treatment, cancer treatment, bioscience, and drug delivery.